The Neglected Belowground Dimension of Plant Dominance. (September 2020) - Ottaviani, Gianluigi; Molina-Venegas, Rafael; Charles-Dominique, Tristan; Chelli, Stefano; Campetella, Giandiego; Canullo, Roberto; Klimešová, Jitka
Abstract : Dominants are key species that shape ecosystem functioning. Plant dominance is typically assessed on aboveground features. However, belowground, individual species may not scale proportionally in relation to their aboveground dimension. This is especially important in ecosystems where most biomass is allocated belowground, including grassy and shrubby biomes.